Mental Health Challenges among Healthcare Workers in Saudi Arabia: A Narrative Review - May Alquwaidi, Ghalib Marwi Alanazi, Sultan Saad AlHarbi, Khaled Manawer AlMutairi, Nader Eid Matar AlMutairi, Ibrahim Muhammad Al-Arij, Amal M. Alsabeg, Abdulmohsin Abdulaziz Alhassan,; Nasser Alotaibi, Aisha Laheg Assiri, Mohammad Sliman Althobaiti, Bassam Saeed Alshehri, Asma Odah Alanazi, Wejdan Talal Sajini, Wejdan Mahmood Abdullah Al Sindi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare workers (HCWs) in Saudi Arabia have faced immense psychological challenges, particularly during the COVID-19 pandemic. The increased workload, fear of infection, social isolation, and emotional exhaustion have contributed to high rates of anxiety, depression, burnout, and post-traumatic stress disorder (PTSD). This review explores the mental health impact on HCWs in Saudi Arabia, examining contributing factors and potential coping mechanisms. The study also highlights the importance of institutional support, workplace interventions, and policy recommendations to improve the psychological well-being of HCWs. By synthesizing findings from existing literature, this review aims to provide a comprehensive understanding of the mental health challenges faced by HCWs in Saudi Arabia and propose strategies to address them.